Historical Roman Genesis and Development in Uzbek Prose - M. Ganiev (Researchparks Publishing, 2022)
The article aims to show the basics of the historical novel in Uzbek literature and its development. Here stated that the tasks of the genre were carried out through folk epics and epics in written literature until the XX century, and in the detecting the theoretical bases of historical work compositions main bases were the opinions of such scientists as Arastu, Gegel, I.Sultonov, A.Rakhimov, D.Kuronov.